Understanding and comparing digital traces - Horsman, Graeme (Taylor & Francis, 2025)
Digital forensic practitioners will encounter digital traces during their examinations which they must take steps to understand. This may involve trying to attribute an ‘activity’ to a trace (what created it) or determine where it came from (its ‘source’) – Trace-to-Activity/Source interpretation. Alternatively, they may need to determine if an activity has taken place on a system by identifying traces denoting it – Activity-to-Trace interpretation. In both instances, practitioners may need to conduct tests and/or identify research which will help them understand a trace, and compare any results of their testing/research to the traces in their casework. This work describes both the Trace-to-Activity/Source and Activity-to-Trace interpretive journeys, as well as the steps contained in both. In addition, six ‘trace comparison criteria’ are proposed and discussed to help those carrying out a trace comparison, notably: ‘trace location’, ‘trace structure’, ‘trace examination method’, ‘trace metadata’, ‘trace content’, and ‘trace context’.
Keywords: Digital forensics; digital trace; digital evidence; testing; interpretation